Radiation principles, protection, and reporting for interventional pulmonology: a World Association of Bronchology and Interventional Pulmonology white paper - Wijma, Inge; Casal, Roberto F.; Cheng, George Z.; Einsiedel, Paul F.; Fantin, Alberto; Hall, David J.; Herth, Felix; Ng, Calvin S. H.; Pritchett, Michael A.; Shah, Pallav L.; Steinfort, Daniel P.; Trisolini, Rocco; et al. (Respiration, 2024)
The use and availability of diverse advanced X-ray based imaging and guidance systems in the field of interventional pulmonology are rapidly growing. This popularity links inextricably to an increase in ionizing radiation use. Knowing ionizing radiation is hazardous, knowledge and competent use of X-ray imaging and guidance systems are important. The globally implemented As Low As Reasonably Achievable (ALARA) principle demands careful attention to minimize radiation exposure while achieving the precise goals of the intervention and imaging therein. To allow careful and targeted weighing of risk against reward while using X-ray based equipment, proper background knowledge of physics as well as imaging system aspects are needed. This white paper summarizes the principles of ionizing radiation which are crucial to enhance awareness and interpretation of dosimetric quantities. Consecutively, a consensus on standards for reporting radiation exposure in interventional pulmonology procedures is indicated to facilitate comparisons between different systems, approaches and results. Last but not least, it provides a list of practical measures, considerations and tips to optimize procedural imaging as well as reduce radiation dose to patients and staff.
Online veröffentlicht: 21. Juli 2024
Gesehen am 20.08.2025